HUBUNGAN PEMBERIAN ASI EKSKLUSIF ENAM BULAN DENGAN KEJADIAN OBESITAS PADA ANAK USIA PRASEKOLAH DI KOTA DENPASAR - Purwaningrum, Ni Made Ari (E-Jurnal Medika Udayana, 2022)
Background : Obesity is the accumulation and excess storage of fat in the body. The prevalences of children obesity is increasing in worldwide. Obesity is influenced by several factors. Exclusive breastfeeding can be a protective factor for obesity. This study is to determine a relationship between six months of exclusive breastfeeding with incidence of obesity in preschool children in Denpasar city. Method : This study was conducted using a case-control method. The research subjects consisted of 84 children divided into case groups of 42 children and control groups of 42 children at TK Saraswati 3, TK Cipta Dharma, TK Santo Yoseph, TK Waturenggong, TK Saraswati 1, TK Kartika VII-13, TK Santo Yoseph 1 , and TK Harapan Bangsa. Result : Based on the results of the bivariate analysis showed that six months of exclusive breastfeeding and the incidence of obesity had a significant relationship with the p value of 0.001 (p?0.05, OR = 0,205). Conclusion : There is a relationship among six months of exclusive breastfeeding with the incidence of obesity in preschool children in Denpasar City. Keywords : Obesity, exclusive breastfeeding, children